Major and minor surgery: Terms used for hundreds of years that have yet to be defined. (June 2021) - Newsome, Kevin; McKenny, Mark; Elkbuli, Adel
Highlights: The terms major and minor surgery are commonly used in scientific literature. The lack of an established distinction between the two terms has major implications on the interpretation of research, clinical practices, and outcomes. Researchers should be cautious when using major and minor surgery to describe procedures unless accompanied by a thorough evidence-based explanation of each category. The terminology may be useful for setting the tone of expectations when communicating with patients and their families, but physicians must weigh this utility against the complications caused by unsuitable use in scientific literature and medical education.